CTA s experiences with youth agripreneurship - Lohento, Ken (Technical Centre for Agricultural and Rural Cooperation, 2018)
Ken Lohento, Senior Programme Coordinator at CTA, shares some insights on why youth is a cross-cutting issue in the activities of the Centre.